1986
DOI: 10.1007/bf02555175
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline phosphatase as a marker of osteoinductive cells

Abstract: Epithelial cells with osteoinductive potential (KB and WISH cell lines, transitional epithelium of several species) are rich in alkaline phosphatase activity. In contrast, cells devoid of osteoinductive ability are low in this enzyme activity. However, there were no differences between the two classes of cells with respect to acid phosphatase activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(47 citation statements)
references
References 19 publications
0
46
0
1
Order By: Relevance
“…When the cells received the exogenous stimulus and the ALPase activity of the cells rose, it seems that the cells Table 1 Chemical formula, the name, and codes of the compounds used in this study are differentiated into cells which form secondary dentin for preventing the stimulus 28) . Mikami et al 29) reported that the solution which soaked polyalkenoate cement suppressed the ALPase activity and the cause seemed to inhibit the cell differentiation.…”
Section: Measurement Of Alkaline Phosphatase Activity (Alpase Activity)mentioning
confidence: 99%
See 1 more Smart Citation
“…When the cells received the exogenous stimulus and the ALPase activity of the cells rose, it seems that the cells Table 1 Chemical formula, the name, and codes of the compounds used in this study are differentiated into cells which form secondary dentin for preventing the stimulus 28) . Mikami et al 29) reported that the solution which soaked polyalkenoate cement suppressed the ALPase activity and the cause seemed to inhibit the cell differentiation.…”
Section: Measurement Of Alkaline Phosphatase Activity (Alpase Activity)mentioning
confidence: 99%
“…When cells have high ALPase activity, it is thought that the cells differentiate into cells with calcification ability 28) . In this study, the ALPase activity of the fibroblasts exposed to the four acids and HQ was lower than that of control, and decreased with increase of their acids and HQ.…”
Section: Alpase Activity Of the Cells Exposed To The Acids And Hqmentioning
confidence: 99%
“…It is well known that ALPase activity increases when cells contact each other. 14,15 Therefore, the seeding number of HPLF was adjusted to 10 6 (a) and 3 × 10 5 (b) cells/dish in DMEM, respectively. Although in the case of 3 × 10 5 cells/dish, HPLF did not make an aggregate, ALPase activity initially increased temporarily for a few days on CPEC and then decreased gradually.…”
Section: Cell Growthmentioning
confidence: 99%
“…It has been used as a valuable marker enzyme of odontoblast-like cells in vitro [30,31], as well as bone-cells [32]. Our subcultured cells expressed ALP activity which was inhibited in a dosedependent manner by F. Sodium fluoride is widely used in the treatment of osteoporosis and one of the responses to F treatment is an increase of the serum ALP activity [33,34].…”
Section: Alkaline Phosphatase Activitymentioning
confidence: 85%